”Homogeneous” second order differential equation: zeros separation principles - RUS, Ioan A. (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper we study the following problems: Problem 1. Let I ⊂ R be an open interval and F : R3 × I → R be a continuous function with, F (0, 0, 0, x) = 0, for all x ∈ I. We consider the following differential equations ... ... Mathematics Subject Classification (2010): 34C10, 12D10, 34B24, 33xx, 34M10.